1982
DOI: 10.1159/000287625
|View full text |Cite
|
Sign up to set email alerts
|

Life Events before the Onset of Rheumatoid Arthritis

Abstract: All female patients seen at a rheumatological clinic within 1 year of the onset of rheumatoid arthritis were referred for psychiatric assessment. There was 1 refusal and 22 patients were seen by the author, a psychiatrist working in the Department of Rheumatology. Psychiatric assessment, combined with a brief survey of important life events in the year before the onset of symptoms, was compared with a similar assessment made on randomly selected age-matched well women, among whom there was also 1 refusal. 12 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
4

Year Published

1988
1988
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 7 publications
0
31
0
4
Order By: Relevance
“…Given this association between RA and the level of Th1 cell immunity, four other findings suggested that an association might exist among SNS activity, ␤ 2 AR stimulation of naive T and/or Th1 cells, and the development and/or progression of RA. First, an increase in disease activity among RA patients was associated with an increase in the level of stress experienced by these patients [79,80], suggesting that a stressinduced increase in norepinephrine release might exacerbate naive and/or Th1 cell activity. Second, single nucleotide polymorphisms have been found to be associated with the ␤ 2 AR expressed by cells of RA patients [81], suggesting that a change in the ␤ 2 AR structure on a naive T and/or Th1 cell may heighten the level of cell responsiveness to norepinephrine.…”
Section: Regulation Of Cd4ϩt Cell-mediated Immunity By Norepinephrinementioning
confidence: 99%
“…Given this association between RA and the level of Th1 cell immunity, four other findings suggested that an association might exist among SNS activity, ␤ 2 AR stimulation of naive T and/or Th1 cells, and the development and/or progression of RA. First, an increase in disease activity among RA patients was associated with an increase in the level of stress experienced by these patients [79,80], suggesting that a stressinduced increase in norepinephrine release might exacerbate naive and/or Th1 cell activity. Second, single nucleotide polymorphisms have been found to be associated with the ␤ 2 AR expressed by cells of RA patients [81], suggesting that a change in the ␤ 2 AR structure on a naive T and/or Th1 cell may heighten the level of cell responsiveness to norepinephrine.…”
Section: Regulation Of Cd4ϩt Cell-mediated Immunity By Norepinephrinementioning
confidence: 99%
“…For example, clinical studies have revealed that the onset and more commonly the exacerbation of rheumatoid arthritis are often preceded by psychological stress [4]. The joints on the paretic side of hemiplegic patients, who later develop rheumatoid arthritis, are completely spared (or develop only mild synovitis) and do not develop erosions or nodules [5], although it is possible that this sparing could be a mechanical consequence of the lack of use of the limb.…”
Section: Introductionmentioning
confidence: 99%
“…There is also much evidence [20] indicating the effects of stress on the immune system. As to the development of arthritis, it has been suggested that severe emotional stress modifies the immune reactions of patients in such a way that the autoimmune process of RA is launched [4], The stress may reduce the body's resistance to some common virus which then precipitates the autoimmune reaction [4]. However, the link between so matic and psychic functions still needs fur ther research.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the question, how far environmental factors such as stressful life events contribute to its causation has been seen of importance. There is evidence that life changes may be the precipitating factors in the onset of rheu matoid arthritis [1,4,5] and JRA [6][7][8][9], Meyerowitz et al [5] state that 'rheumatoid arthritis may tend to develop in an individ ual who may be identifiable through a cluster of personality traits. Such an individual may develop the disease in a setting of psycholog ical stress.…”
mentioning
confidence: 99%